1998
DOI: 10.1002/(sici)1099-1395(199804)11:4<232::aid-poc984>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Molecular orbital calculations on the P?S bond cleavage step in the hydroperoxidolysis of nerve agent VX

Abstract: The P-S bond cleavage process in the hydroperoxidolysis of a model system for the nerve agent VX was studied using ab initio and semiempirical molecular orbital methods. Aqueous solvation effects were included through single-point calculations using the semiempirical SM5.2PD/A continuum solvation model and geometries optimized at the HF/MIDI! level of theory. The predominant pathway for P-S bond cleavage involves pseudorotation of a low-energy trigonal bipyramidal intermediate followed by apical ligand ejectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 88 publications
1
32
0
Order By: Relevance
“…The SES approximation has served as the basis of a number of previous investigations ,,,,,,, of solvation effects on barriers using conventional or variational transition state theory. Some recent examples employing implicit-solvent methods are given in Table , which uses the same conventions as Table .…”
Section: 12 Ses and Esp Applicationsmentioning
confidence: 99%
“…The SES approximation has served as the basis of a number of previous investigations ,,,,,,, of solvation effects on barriers using conventional or variational transition state theory. Some recent examples employing implicit-solvent methods are given in Table , which uses the same conventions as Table .…”
Section: 12 Ses and Esp Applicationsmentioning
confidence: 99%
“…Theoretical calculations have demonstrated that a stable pentacoordinate intermediate is formed during P-S bond peroxidolysis of an analogue of VX in aqueous solution. 18 Whether this also occurs during the hydrolysis of phosphorothiolate pesticides, which differ in that they do not possess any phosphonate bonds, is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Fig 9. Reaction coordinate diagram for the addition-elimination process which was not observed during the gas phase reaction of HOO − anion with DMMP.…”
mentioning
confidence: 99%